Artificial Immune Algorithms For University Examination Timetabling. - Malim, Muhammad Rozi; Khader, Ahmad Tajudin; Mustafa, Adli (2005)
The examination timetabling is known to be a highly constrained optimization problem. Metaheuristic approaches (simulated annealing, tabu search, and evolutionary algorithms) have successfully been applied to solve the problem.